2020
DOI: 10.1038/s42003-020-1096-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of muntjac deer genome and chromatin architecture reveals rapid karyotype evolution

Abstract: Closely related muntjac deer show striking karyotype differences. Here we describe chromosome-scale genome assemblies for Chinese and Indian muntjacs, Muntiacus reevesi (2n = 46) and Muntiacus muntjak vaginalis (2n = 6/7), and analyze their evolution and architecture. The genomes show extensive collinearity with each other and with other deer and cattle. We identified numerous fusion events unique to and shared by muntjacs relative to the cervid ancestor, confirming many cytogenetic observations with genome se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 93 publications
3
42
1
3
Order By: Relevance
“…These discoveries shed lights on the chromatin regulatory roles of chromosome rearrangement events during species evolution. It is noteworthy that a recent study comparing only M. reevesi and M. muntjak vaginalis without other species as control, concluded that the compartments are not well conserved between M. reevesi and M. muntjak vaginalis 52 , which is in contrast to our results. We downloaded their data and conducted careful comparison and found their analyses and conclusions had problems.…”
Section: Discussioncontrasting
confidence: 99%
“…These discoveries shed lights on the chromatin regulatory roles of chromosome rearrangement events during species evolution. It is noteworthy that a recent study comparing only M. reevesi and M. muntjak vaginalis without other species as control, concluded that the compartments are not well conserved between M. reevesi and M. muntjak vaginalis 52 , which is in contrast to our results. We downloaded their data and conducted careful comparison and found their analyses and conclusions had problems.…”
Section: Discussioncontrasting
confidence: 99%
“…They would be in isolation since the reproductive fitness of a potential hybrid could be greatly aggravated by chromosomal imbalance, and thus being practically sterile ( Galindo et al, 2021 ). This is observed in hybrids or populations with the presence of heterozygous tandem fusion, which are considered highly deleterious chromosomal rearrangements, rapidly removed or fixed at meiosis during speciation ( King, 1993 ; Yang et al, 1997 ; Dobigny et al, 2017 ; Mudd et al, 2020 ). Although molecular data indicated the absence of reciprocal monophyly between Paraná and Carajás and suggested both as a single MOTU in the GMYC analyses, this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Fourfold degenerate bases of one-to-one orthologs were obtained and reformatted from the MAFFT alignment as described in Mudd et al 145 (Supplementary Note 4). The maximumlikelihood phylogeny was obtained with RAxML 150 (v8.2.11) using the GTR+Gamma model of substitution with outgroup Ambystoma mexicanum.…”
Section: Phylogeny and Estimation Of Sequence Divergencementioning
confidence: 99%
“…Customized scripts 145 were used to extract pairwise alignments from the ROAST-merged MAF file and converted into runs of collinearity. The runs of collinearity were visualized with Circos 153 (v0.69-6) (Supplementary Note 4).…”
Section: Chromosome Evolutionmentioning
confidence: 99%